Awareness and prevalence of self-reported benign prostatic hyperplasia: a cross-sectional study in Saudi Arabia - Alzahrani, Fahad; Madkhali, Osama A.; Khardali, Amani; Alqahtani, Saad S.; Hijri, Abdulrahman M.; Alaqil, Mazen A.; Madkhali, Yaseen A.; Otayn, Zakaria Y.; Syed, Nabeel Kashan (Frontiers in Public Health, 2024)
Background Benign prostatic hyperplasia (BPH) is a prevalent condition in older men, causing significant morbidity. Despite recent progress, essential concerns of the disease remain under-researched. This study aims to assess knowledge and estimate self-reported prevalence of BPH in Saudi Arabian men. Understanding BPH prevalence in Saudi Arabia is essential for healthcare planning, resource allocation, public awareness, early detection, intervention, research, and addressing regional variations. Method A cross-sectional study was conducted from February to May 2022 using a validated questionnaire. Univariate and multivariate statistical methods assessed knowledge of BPH among 559 adult Saudi men (mean age: 47.2 years) and its association with demographic variables. Results The self-reported prevalence rate of BPH for Saudi Arabian men was 12.0%. Most adults (74.2%) were aware that BPH is a risk factor for prostate cancer and 75% were aware of the increased risk of BPH in older people. Furthermore, 44.5% of participants associated nocturia with BPH, while 76.6% related urinary tract infection (UTI) with BPH. The study demonstrated a significant association between BPH awareness and marital status (p = 0.02), level of education (p = 0.02), and employment status (p = 0.04). Conclusion While men in Saudi Arabia generally had sufficient knowledge about BPH, there was a knowledge gap regarding certain risk factors like obesity and cardiac diseases. To address this, an educational program should be developed for both the general population and those at high risk of BPH.